The predistribution agenda: tackling inequality and supporting sustainable growth (London, 2015)
"The concept of predistribution is increasingly setting the agenda in progressive politics. But what does it mean? The predistributive agenda is concerned with how states can alter the underlying distribution of market outcomes so they no longer rely solely on post hoc redistribution to achieve economic efficiency and social justice. It therefore offers an effective means of tackling economic and social inequality alongside traditional welfare policies, emphasising employability, human capital, and skills, as well as structuring markets to promote greater equity. This book examines the key debates surrounding the emergence and development of predistributive thought with contributions from leading international scholars and policy-makers."